Effectiveness of The Familly of Hope Program - Dwi Novia, Santi; Mursyidah, Lailul (Indonesian Journal of Public Policy Review, 2022)
The purpose of this study was to describe and analyze the Effectiveness of the Family Hope Program in Banjarbendo Village, Sidoarjo District, Sidoarjo Regency. The research method used is descriptive research with a qualitative approach. The data collection techniques used are interviews, observation and documentation with one key informant including the PKH supervisor in Banjarbendo Village and informants including the Head of the Welfare Section, Head of the Family Hope Program Division, Sidoarjo Social Service, recipient participants PKH benefits. The data analysis technique in this research is data collection. data reduction, data presentation and drawing conclusions. The results of the study can be seen that in the that in achieving goals, it has been able to achieve its goals especially in the education and health sectors, and the impact it has has a positive impact on PKH beneficiary families.